(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
Innovation is the driving force that is able to create and transform products, processes, and organization in the health system. Innovation in the field of pharmaceutical assistance covers a wide spectrum of aspects, from drug discovery to pharmaceutical care, contributing to the improvement in treatments through novel drugs or methods. This work will present the major characteristics of innovation with special emphasis on aspects pertaining to pharmaceutical assistance. The types and models of innovation, as well as the interaction between academia and industry, will be presented with examples of successful products and methods. In addition, the challenges and perspectives for innovation in pharmaceutical assistance will be discussed with a focus on drug discovery.